A risky business? Comparing the harms of alcohol and other recreational drugs. Issue 2 (26th March 2021) - Nutt, David
Abstract : David Nutt, author of Drugs Without the Hot Air, explains how multi‐criteria decision analysis has been used to assess harms caused by legal and illegal drugs Abstract : David Nutt, author of Drugs Without the Hot Air, explains how multi‐criteria decision analysis has been used to assess harms caused by legal and illegal drugs.